Impact of Epstein-Barr virus infection on the development and prognosis of allergic purpura - Zhao, Zinian; Zhang, Ying; Han, Jing; Ren, Rong; Li, Guangming; Yang, Jinyu (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to examine the impact of Epstein-Barr virus (EBV) infection on the occurrence and prognosis of Henoch-Schönlein purpura (HSP). Methodology: A total of 120 children diagnosed with HSP were selected as the experimental group, and 100 healthy children who underwent physical examinations were the control group. We compared renal function markers and quantified 24-hour urine protein in HSP children with different EBV infection statuses, and analyzed the association between EBV infection and Henoch-Schönlein purpura nephritis (HSPN). Results: The detection rate of EBV-DNA load in the experimental group (30.83%) was significantly higher than that in the control group (10.00%) (p < 0.05). Among children with HSP, the detection rate of EBV-DNA load was significantly higher in those with abdominal involvement compared to those with joint or mixed types (p < 0.05). Serum levels of serum creatinine, blood urea nitrogen, and urine protein quantification were significantly higher in the EBV-positive group than in the EBV-negative group (p < 0.05). The detection rate of EBV-DNA load was significantly higher in the HSPN group compared to the non-HSPN group (p < 0.05). The detection rate of EBV-DNA load was significantly higher in the recurrence group than in the non-recurrence group (p < 0.05), and it was also higher in the relapse group compared to the non-relapse group (p < 0.05). Conclusions: EBV infection is associated with the development of HSP; and gastrointestinal, joint, and renal damage. It is also an early warning sign for disease recurrence, which highlights its clinical significance.